Female Ex-Offender Perspectives on Drug Initiation, Relapse, and Desire to Remain Drug Free. Issue 2 (April 2016) - Nyamathi, Adeline M.; Srivastava, Neha; Salem, Benissa E.; Wall, Sarah; Kwon, Jordan; Ekstrand, Maria; Hall, Elizabeth; Turner, Susan F.; Faucette, Mark
Abstract : ABSTRACT: Recently released homeless women residing in temporary residential drug treatment (RDT) programs are at a critical juncture in the process of recovery, transition, and reentry. The purpose of this study was to explore factors influencing initial use of drugs and relapse triggers among a sample of incarcerated women exiting jails and prisons, residing in an RDT program, and preparing for reentry into their communities. Among this population, relapse to drug use and recidivism are common. A qualitative study was conducted utilizing focus groups to understand the perspectives of formerly incarcerated, currently homeless women residing in an RDT program. Content analysis generated the development of three broad categories: (a) factors associated with first drug use, (b) factors involved in relapse, and (c) factors influencing desire to remain drug free. A discussion follows highlighting the importance of targeted interventions at RDT sites that integrate physical, psychological, and social needs to optimize reentry into communities. This includes a focus on building self-esteem and life skills and providing access to resources such as housing, employment, and healthcare.